Reproductive physiology of teleost fishes : - Sundararaj, B. I. (FAO, 1981)
This important publication provides, for the first time, a comprehensive review of knowledge of reproductive seasonality in teleosts. It addresses why a particular species should show such seasonality, and how environmental cues act as regulators to ensure that reproductive maturation and breeding occur at the optimum time. The book considers the ultimate factors responsible for the evolution of reproductive seasonality in fish.